2016
DOI: 10.1590/0103-8478cr20150534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osmotic dehydration on bioactive compounds, antioxidant capacity, color and texture of fruits and vegetables: a review

Abstract: Osmotic dehydration (OD) is a conservation technique applied to foodstuffs, which promotes partial reduction of water, extends their shelf life and reduces both post-harvest losses and changes in product characteristics. Currently, it has been given emphasis on trying to understand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…Optimum temperature activity of many enzymes is in the range 20–30 °C. The use of the low temperatures associated with the protector effect that sugar has in some pigments can minimize these alterations during OD process (Landim et al 2016 ).The fruit pieces surrounded by sucrose solution are prevented against enzymatic and oxidative browning. Garcia-Noguera et al ( 2014 ) showed that osmotic dehydration enhanced the color in strawberry samples, especially after prolonged ultrasonic exposure and using high sucrose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Optimum temperature activity of many enzymes is in the range 20–30 °C. The use of the low temperatures associated with the protector effect that sugar has in some pigments can minimize these alterations during OD process (Landim et al 2016 ).The fruit pieces surrounded by sucrose solution are prevented against enzymatic and oxidative browning. Garcia-Noguera et al ( 2014 ) showed that osmotic dehydration enhanced the color in strawberry samples, especially after prolonged ultrasonic exposure and using high sucrose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, according to Atares et al [32], during the osmotic treatment of the banana in the high concentrated sucrose solution reduces the transport of bioactive compounds from the product to the solution, due to the sucrose barrier created on the surface of the sample, which is responsible for the total actioxidant activity preservation of the product. In addition, the penetration of the osmotic solution into the plant tissue prevents the enzyme-substrate interaction due to the limited concentration of oxygen and moisture in the current enzyme environment, thereby preventing the oxidation of antioxidant compounds through enzymatic activity [33]. Inhibition of possible enzymatic activity, contributes to the preservation of the present antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] It is done by immersing food materials either in whole or units into hypertonic solution which allows diffusion of moisture from the food material into the solution concurrently with solid impregnation into the food material. 10,[17][18][19][20][21][22] This transfer could also be accompanied by leaching of organic acids, sugars, salts, fragrances, colourants and minerals from the food materials into the solution. 16,23 Sugar and salt solutions are usually employed with sucrose and sodium chloride as the mostly used.…”
Section: Introductionmentioning
confidence: 99%